FIGURATIVE LANGUAGE APPLIED IN MELANIE MARTINEZ’S K-12 ALBUM - Darmawan, Anisa Safira; Widyaningrum, Agnes (LINGUAMEDIA Journal, 2024)
This research paper is focused to find figurative language in the lyrics of the song "K - 12" by Melanie Martinez. The researcher uses Perrine’s theory to find out the most dominant types of figurative language, implied meaning, and the type of figurative language.  This study is a descriptive study by applying text oriented approach in this research to obtain the require d data.  The song lyrics are categorized into 7 types of figurative languages, and interpreted to find the implied meaning of it. There are 7 types of figurative language used in the lyrics of   the   song   "K - 12"   by   Melanie   Martinez   with   a   total   of   7   metaphor, 2 personifications, 7 hyperboles, 8 imageries, 8 ironies, 5 symbol, and 2 paradoxes. Keywords : Perrine’s figurative language, literature, song lyric, text-oriented approach, Melanie Martinez K-12 album